Space‐Time Patterns of Meteorological Drought Events in the European Greater Alpine Region Over the Past 210 Years. Issue 11 (28th November 2017) - Haslinger, K.; Blöschl, G.
Abstract: Droughts may have tremendous impacts on humans. However, the space‐time characteristics of droughts are not very well understood, as case studies usually focus on individual drought events. Here we investigate the spatiotemporal drought characteristics of a large sample of events over the past 210 years in the Greater Alpine Region of Central Europe. We use monthly precipitation data, and flag, for each grid point, time steps with precipitation below a 20% percentile. We then propose a new method that detects drought events by connecting the flagged elements to space‐time drought regions. In contrast to the traditional drought indices that are based on a fixed, prescribed time window, this method is able to identify droughts of different durations in an objective way. The data show multidecadal variations of drought frequency, duration, intensity, and severity, but no consistent trends over the 210 year period. The top 5% of events in terms of their severity show a shift in seasonality from winter/spring events in the late nineteenth century toward autumn events during the last decades of the twentieth century. The most severe events center either in the Northwest or in the Southeast of the region analyzed. We found no significant correlations of drought frequency, duration, intensity, and severity with the temperature increases in the past three decades. Dry springs significantly enhance temperatures during summer droughts, suggesting a soil moisture‐temperature feedback. Key Points: A new method is proposed for detecting atmospheric drought events in terms of their frequency, duration, intensity, and severity Multidecadal variations of drought frequency, duration, intensity, and severity over the past 210 years exist in the GAR, but no trends Most severe events center either around the Northwest or the Southeast of the GAR